Construction of a high-density mutant library in soybean and development of a mutant retrieval method using amplicon sequencing. (December 2015) - Tsuda, Mai; Kaga, Akito; Anai, Toyoaki; Shimizu, Takehiko; Sayama, Takashi; Takagi, Kyoko; Machita, Kayo; Watanabe, Satoshi; Nishimura, Minoru; Yamada, Naohiro; Mori, Satomi; Sasaki, Harumi; et al.
Abstract Background Functions of most genes predicted in the soybean genome have not been clarified. A mutant library with a high mutation density would be helpful for functional studies and for identification of novel alleles useful for breeding. Development of cost-effective and high-throughput protocols using next generation sequencing (NGS) technologies is expected to simplify the retrieval of mutants with mutations in genes of interest. Results To increase the mutation density, seeds of the Japanese elite soybean cultivar Enrei were treated with the chemical mutagen ethyl methanesulfonate (EMS); M2 seeds produced by M1 plants were treated with EMS once again. The resultant library, which consisted of DNA and seeds from 1536 plants, revealed large morphological and physiological variations. Based on whole-genome re-sequencing analysis of 12 mutant lines, the average number of base changes was 12, 796 per line. On average, 691 and 35 per line were missense and nonsense mutations, respectively. Two screening strategies for high resolution melting (HRM) analysis and indexed amplicon sequencing were designed to retrieve the mutants; the mutations were confirmed by Sanger sequencing as the final step. In comparison with HRM screening of several genes, indexed amplicon sequencing allows one to scan a longer sequence range and skip screening steps and to know the sequence information of mutation because it uses systematic DNA pooling and the index of NGS reads, which simplifies the discovery of mutants with amino acid substitutions. Conclusions A soybean mutant library with a high mutation density was developed. A high mutation density (1 mutation/74 kb) was achieved by repeating the EMS treatment. The mutation density of our library is sufficiently high to obtain a plant in which a gene is nonsense mutated. Thus, our mutant library and the indexed amplicon sequencing will be useful for functional studies of soybean genes and have a potential to yield useful mutant alleles for soybean breeding.